2019
DOI: 10.1177/1545968319855038
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activations During Optokinetic Stimulation in Acute Right-Hemisphere Stroke Patients and Hemispatial Neglect: An fMRI Study

Abstract: Objective. Leftward optokinetic stimulation (OKS) is a promising therapeutic approach for right-hemisphere stroke patients with left hemispatial neglect. We questioned whether the putative neural basis is an activation of frontoparietal brain regions involved in the control of eye movements and spatial attention. Methods. We used functional magnetic resonance imaging to investigate brain activations during OKS in acute right-hemisphere stroke patients (RHS, n = 19) compared with healthy control subjects (HC, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…A large number of studies have been published for each approach. Since this is not a systematic review of neglect treatments, we will focus on the most promising recently proposed rehabilitation methods, although other effectivebut less employedtechniques have been investigated to treat the disorder, such as eye-patching, 73 caloric vestibular stimulation, 74 visuomotor imagery, 75 mirror therapy, 76 TENS, 77 Optokinetic Stimulation [78][79][80] and the Constraintinduced movement therapy. 81,82 Specifically, we conducted a MEDLINE literature research on the use of prismatic adaptation, non-invasive brain stimulation and virtual reality in USN rehabilitation.…”
Section: Rehabilitation Methodsmentioning
confidence: 99%
“…A large number of studies have been published for each approach. Since this is not a systematic review of neglect treatments, we will focus on the most promising recently proposed rehabilitation methods, although other effectivebut less employedtechniques have been investigated to treat the disorder, such as eye-patching, 73 caloric vestibular stimulation, 74 visuomotor imagery, 75 mirror therapy, 76 TENS, 77 Optokinetic Stimulation [78][79][80] and the Constraintinduced movement therapy. 81,82 Specifically, we conducted a MEDLINE literature research on the use of prismatic adaptation, non-invasive brain stimulation and virtual reality in USN rehabilitation.…”
Section: Rehabilitation Methodsmentioning
confidence: 99%
“…Cutoff scores have been previously defined for neglect tests. According to these scores 9 out of 11 patients showed pathological performance in both, cancellation task (cutoff: CoC = 0.083) [ 47 ], and LBT (cutoff: ≥ 6.5 mm) [ 48 ]. Two patients exhibited spatial neglect primarily in bells test (CoC: 0.728 and 0.548), but performed close to LBT cutoff score (LBT: 5 and 6 mm deviation from the true center).…”
Section: Resultsmentioning
confidence: 99%
“…Even if both treatments are bottom up-techniques, they rely on different neural and cognitive mechanisms. Imaging studies in USN patients have revealed that the OKS activates bilaterally frontoparietal regions (FEF and IPS) that have been spared from brain damage and are functionally involved in both oculomotor control and spatial attention [68]. The OKS stimulates the pursuit system [69], and the smooth pursuit eye movements seem to be the key factor of the OKS treatment [70].…”
Section: Discussionmentioning
confidence: 99%